Research on Relationship Between VC and Innovation Based on a European Panel of VC Investments - Jun, Zhao Yuan (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
In this paper we search for evidence signifying whether VC activity is demand or supply stimulated. Namely, we examine whether innovation and entrepreneurship are fostered by Venture Capital (VC) investments or whether innovative entrepreneurship is a precondition of a VC involvement. Based on a European panel of VC investments, we test the direction of causality between VC and innovation (provide by annual patent applications at the European Patents Office). We present evidence indicating that causality runs from patents to VC suggesting that, in Europe, innovation seems to create a demand for VC and not VC a supply of innovation. In this sense, innovative ideas seem to lack more than funds in Europe. We explain our findings on the basis of information asymmetry issues and irreversibility considerations of VC investments.